Elaboração de conserva de pirarara (Phractocephalus hemioliopterus Bloch & Schneider,1801) - Alves, Cristian Soares Sampaio (Brasil, 2024)
Fishing is one of the main food sectors in the Amazon, with a focus on researching market viability and economic acceptance. The catfish pirarara (Phractocephalus hemioliopterus) was chosen, studied, and subjected to sensory testing, as well as methodological analysis of the fish's physical, chemical, and nutritional aspects. pirarara is commonly found in the Amazon fish market, but due to regional prejudice against most catfish species, it is not widely distributed. The development of pirarara preserves aims to add value to the fish, as it is a protein-rich product with low fat content and excellent levels of certain vitamins. It holds significance in the Amazon market as a local product and represents a considerable-sized fish for trade, where research assists in the viability of underutilized siluriform fishes. The preservation of pirarara and other siluriform fishes can facilitate access to these proteins in regions far from major urban centers. Research and the development of new products based on Amazonian fish, such as pirarara preserves, have the potential to boost the regional economy, valorizing the natural resources of the Amazon and promoting socio-environmental sustainability. These initiatives represent business opportunities and contribute to the preservation of the region's aquatic ecosystems.